Uji Aktivitas Propionibacterium Acnes Pada Formulasi Sabun Wajah Ekstrak Akar Bajakah (Spatholobus littoralis Hassk.) - desy putri pontianingsih mattobii; Heny Puspasari; Adhisty Kharisma Justicia (Jurnal Farmasi Ma Chung: Sains, Teknologi, dan Klinis Komunitas, 2025)
Bajakah root (Spatholobus littoralis Hassk) is a plant that has antibacterial properties. Bajakah root plant (Spatholobus littoralis Hassk) contains saponins, alkaloids, flavonoids, tannins, and phenols. This study aims to determine the activity on Propionibacterium acnes bacteria. In this study, the samples tested were 5% ethanol extract facial soap formula, soap base (negative control), and acnes facial soap (positive control). Testing antibacterial activity against Propionibacterium acnes bacterial growth using the diffusion method. The results of the study showed that the 5% bajakah root ethanol extract facial soap formula obtained could inhibit Propionibacterium acnes bacteria, namely in the positive control of 16.81 mm, F1 of 4.7 mm, F2 of 4.27 mm, F3 of 4.7 mm, and negative control of 0 mm. These results show that the facial soap formula of 5% bajakah root ethanol extract is included in the weak category of inhibitory power.